The Existence of Personal Data Protection in the Digital Era Based on Indonesia’s Electronic Information and Transactions Law - Gema Rahmadani; Yovani Zela (Program Pascasarjana UIN Sumatera Utara Medan, 2019)
The rapid development of digital technology has significantly increased the use of electronic media in everyday life, making personal data protection an important issue in Indonesia. Personal data contains confidential information that must be protected to ensure individual privacy and security. However, the increasing use of digital platforms has also contributed to a rise in cybercrimes, including data breaches, hacking, identity theft, and misuse of personal information. Therefore, legal protection of personal data is necessary to provide legal certainty and maintain public trust in electronic systems. This study aims to analyze the existence of personal data protection in the digital era through the implementation of Indonesian regulations, particularly the Electronic Information and Transactions Law (ITE Law). This research uses a normative juridical method with a statutory approach by examining laws and regulations related to personal data protection. Data sources consist of primary legal materials, including legislation, and secondary legal materials obtained from books and previous studies. The results show that the ITE Law provides legal protection for personal data through provisions regulating consent, confidentiality, electronic system management, and sanctions against unauthorized access or misuse of data. However, the implementation of personal data protection remains insufficient due to weak law enforcement and the increasing number of data leakage cases. Therefore, stronger supervision, improved cybersecurity systems, and increased public awareness regarding digital literacy are needed. Effective collaboration between the government, electronic system providers, and society is essential to strengthen personal data protection and ensure a secure digital environment in Indonesia.